1995
DOI: 10.1029/95ja00434
|View full text |Cite
|
Sign up to set email alerts
|

Statistical survey of auroral latitude Pc 5 spectral and polarization characteristics

Abstract: Recent magnetometer and HF radar observations have indicated the existence of multiple, discrete field line resonances with remarkably stable frequencies of 1.3, 1.9, 2.6, and 3.4 mHz, apparently driven by MHD waveguide/cavity modes in the magnetosphere. Given the dynamic nature of the magnetosphere, the apparent stability of these frequencies is difficult to understand, and it is therefore important to examine this question on the grounds of a larger database. In this paper we present a statistical survey of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
71
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 25 publications
9
71
1
Order By: Relevance
“…Using 1 year of data from five CANOPUS magnetometer stations, Ziesolleck and McDiarmid [1995] examined the spectral and polarization characteristics of'auroral latitude Pc5 pulsations at all local times. Although they found further evidence of discrete FLRs, they also showed that the apparently stable frequencies of 1.3, 1.9, 2.6, and 3.4 mHz did not seem particularly distinguished from other Pc5 signal frequencies.…”
Section: Introduction They Demonstrated That Very Similar Spectral Chmentioning
confidence: 99%
“…Using 1 year of data from five CANOPUS magnetometer stations, Ziesolleck and McDiarmid [1995] examined the spectral and polarization characteristics of'auroral latitude Pc5 pulsations at all local times. Although they found further evidence of discrete FLRs, they also showed that the apparently stable frequencies of 1.3, 1.9, 2.6, and 3.4 mHz did not seem particularly distinguished from other Pc5 signal frequencies.…”
Section: Introduction They Demonstrated That Very Similar Spectral Chmentioning
confidence: 99%
“…In addition, studies of individual events reported evidence of oscillations at the cavity/waveguide mode frequencies, which were associated with SW pressure pulses and extended to a major portion of the Earth's magnetosphere, confirming the global character of these fluctuations (Shimazu et al, 1995;Villante et al, 1998;Lepidi et al, 1999). It was observed that, at auroral latitudes, low-frequency pulsations show a clear morning/afternoon asymmetry, with an higher occurrence rate in the morning (Rostoker and Sullivan, 1987;Ziesolleck and McDiarmid, 1995;Chisham and Orr, 1997;Mathie et al, 1999) and that afternoon pulsations are driven dominantly by sporadic impulses in the SW (Rostoker and Sullivan, 1987). Consistent with the theory by Mann et al (1999), who investigated the energization of waveguide modes by magnetosheath flows on the magnetopause flanks, and with the observations by Mathie et al (1999) and Matthie and Mann (2000), the observed morning/afternoon asymmetry can be explained in terms of a greater stability of the postnoon magnetopause to shear-flow instabilities than the dawn flank; in this sense, pulsations driven by magnetopause instabilities during intervals of enhanced SW speed occur predominantly in the morning, while impulsively driven pulsations may extend over a wide range of local times.…”
Section: Introductionmentioning
confidence: 55%
“…The question is how often these solar-windinduced magnetic pulsations contribute to the pulsations observed on the ground by radar or magnetometers. Most statistical studies of mHz-range pulsations on the ground (e.g., Ziesolleck and McDiarmid, 1995) have not fully incorporated solar wind data. It is of great importance to examine the state of the solar wind at times when magnetic pulsations are observed on the ground.…”
Section: Pc 5 Wavesmentioning
confidence: 99%
“…Ziesolleck and McDiarmid (1995) present a critical examination of the CMS frequencies based on the CANOPUS magnetometer data covering L 4.2±12.3. Although they con®rm the signature of multiple discrete ®eld-line resonances, they do not ®nd the pulsation frequencies to be as stable as claimed from radar observations (Samson et al, 1991;Walker et al, 1992), except perhaps for the 1.9 mHz component.…”
Section: Pc 5 Wavesmentioning
confidence: 99%